Sex‐mismatched red blood cell transfusions and mortality: A systematic review and meta‐analysis. Issue 5 (23rd May 2019) - Zeller, Michelle P.; Rochwerg, Bram; Jamula, Erin; Li, Na; Hillis, Christopher; Acker, Jason P.; Runciman, Ryan J. R.; Lane, Shannon J.; Ahmed, Naveen; Arnold, Donald M.; Heddle, Nancy M.
Abstract : Background and Objectives: Selection of a compatible red blood cell (RBC) unit does not include matching for donor sex. This systematic review and meta‐analysis aims to summarize the evidence examining the impact of sex‐mismatched RBC transfusion on recipient mortality. Materials and Methods: Ovid MEDLINE, Ovid EMBASE, CINAHL, PubMed, Web of Science and the Cochrane Database of Systematic Reviews were searched from inception up to 23 November 2018. Randomized controlled trials and observational studies were included in the search. Eligible studies reported on the impact of sex‐matched compared to sex‐mismatched RBC transfusion on recipient mortality. Two investigators independently extracted data and assessed study quality. A three‐level meta‐analytic model was applied to emphasize the unknown dependence among the effect sizes. Results: Five retrospective observational studies ( n = 86 737) were included; no RCTs were found. Sex‐mismatched RBC transfusions were associated with a higher risk of death compared with sex‐matched transfusions (pooled hazard ratio [HR]: 1·13; 95% confidence interval [CI]: 1·02–1·24). In the subgroup of cardiovascular surgery ( n = 57 712), there was no significant increase in mortality with sex‐mismatched transfusions (pooled HR: 1·08; 95% CI: 0·95–1·22). The data were prone to confounding, selection bias and reporting bias. Certainty of the evidence was very low. Conclusion: Sex‐mismatched RBC transfusions were associated with an increased risk of death in this pooled analysis. However, the certainty of the evidence was very low from observational studies. The need to match donor and recipient sex for transfusions requires further investigation because of the potential widespread impact.